SUSTAINABLE SOCIO-RELIGIOUS HARMONY DEVELOPMENT IN MALAYSIA: AN INTERPRETIVE STRUCTURAL MODELLING FOR MULTI-RELIGIOUS SOCIETY - Abdullah, Muhammad Ridhuan Tony Lim; Al-Amin, M Nuri; Ur-Rahman, Abd; Baharuddin, Azizan; Ahmad, Zaid (Journal of Al-Tamaddun, 2017)
The subject of inter-religious relationship among different religious adherents is crucial in determining social peace and harmony in a multi religious country like Malaysia. The aim of this research is to develop a sustainable socio-religious harmony development model of the Malaysian multi-religious society based on its critical and significant factors. The study capitalized on experts' views and adopted the Design and Development approach as methodology which was conducted in three phases. The first phase utilized the Fuzzy Delphi technique to develop the main socio-religious harmony factors. The outcome of this phase provided the pertinent socio-religious harmony factors to be used for the model development. The second phase adopted the Interpretive Structural Modelling technique to develop the socio-religious harmony model based on the factors determined by the experts. The third phase was the evaluation and the interpretation of the model through the development of the Conica matrix to further analyze the strength and classification of each factor in the model. The findings of Phase one finalized 23 socio-religious harmony factors. Phase two resulted in the model showing the network of factor relationships which proposed factors and clusters of factors which need to be addressed in sequence to develop socio-harmony among religious adherents. The output of phase three indicated that the model showed the factors "Mutual respect", "Rights and freedom of practicing religious teachings", "Inter-religious social justice towards other religion", "Awareness on others' beliefs", and "Peaceful feeling" were proposed to be leading factors to be addressed first. The experts agreed that the network of factors could be divided into three phases: Initiation Phase (n= 10), Intervening phase (n= 3), and Sustaining Phase (n=10). These findings could implicate in the key elements to develop socio-harmony among religious adherents as reference for the relevant authorities to improve the situation appropriately to the critical element of relation shown from the result of the model.